2020
DOI: 10.24996/ijs.2020.61.10.19
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogeological System of Injana Formation in Salahaddin Governorate/ Iraq

Abstract: Injana Formation is the most extended geological formation in Salahaddin Governorate/ Iraq. About 10% of the studied area is covered by the outcrops of the formation as a recharge area. The formation is a subsurface within the unsaturated zone in 5% of the total studied area, while it exists within the saturated zone in about 85%; it is a major confined groundwater aquifer. Therefore, the hydrogeological system of the layers needs to be re-evaluated to describe the successions of aquifers and confining layers … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 2 publications
0
4
0
Order By: Relevance
“…The average EW was 44.80 g, EN was 109.32 eggs per hen and EM was 4887.72 g for the first 24 weeks of the laying period. In the study reported by Abdulla[19], EN recorded for 20 weeks of laying, BWSM, EW and daily EM in two strains of Iraqi local chickens was about 81.97 eggs per hen, 1252.…”
mentioning
confidence: 87%
See 1 more Smart Citation
“…The average EW was 44.80 g, EN was 109.32 eggs per hen and EM was 4887.72 g for the first 24 weeks of the laying period. In the study reported by Abdulla[19], EN recorded for 20 weeks of laying, BWSM, EW and daily EM in two strains of Iraqi local chickens was about 81.97 eggs per hen, 1252.…”
mentioning
confidence: 87%
“….1088/1755-1315/1262/7/072017 6 surrounding flocks of study. In many previous research[15][16][17][18][19][20][21][22][23], the genetic progress was achieved but not shown in the phenotypic level in Iranian local chickens under selection for various economical traits.…”
mentioning
confidence: 99%
“…This has been achieved not only by reducing cell elongation but also by reducing the rate of cell division and physiologically regulating plant height [10]. Alar (Daminozide) is a fast-moving compound that moves to all parts of the plant, it is found in several trade names such as Alar-85, Kylar-85, B-Nine and Succinic Acid, and it may exist freely or in the form of ionized acid and cause obstruction of growth and early flowering of some plants [11,12]. The effect of alar varies according to the method of use, the intensity and quality of lighting, the temperature of the night and day, the type of cultivation medium when the addition is through the soil [13] and the molecular formula of the alar is C 6 H 12 N 2 O 3 , and its molecular weight is 160, and its chemical name is 2,2 dimethyl hydrazide Succinic Acid [14].…”
Section: Introductionmentioning
confidence: 99%
“…While of the Injana formation (Upper Miocene). It unfolds in a narrow space, especially along the southwestern edge of the region, and consists of layers of clay, marl, and sandstone [8], [9].…”
Section: Introductionmentioning
confidence: 99%